Physical properties and processes in the Perth Canyon, Western Australia: Links to water column production and seasonal pygmy blue whale abundance - Rennie, Susan; Hanson, C.; McCauley, Robert; Pattiaratchi, C.; Burton, C.; Bannister, J.; Jenner, C.; Jenner, M. (Elsevier, 2009)
The oceanography of the Perth Canyon, off southwestern Australia, was examined through two major field excursions in austral spring/summer 2003/2004 combined with previous results from field analysis and numerical simulations. Water properties were used to identify water masses and vertical displacement. The field cruises and numerical simulation indicated unique circulation features of the Leeuwin Current and Undercurrent within the canyon associated with the topographic features. The input of nutrients to the euphotic zone occurred sporadically as the Leeuwin Current generally suppressed upwelling, although the Perth Canyon had increased nutrient concentrations within its rims. The distribution of chlorophyll in the surface layers indicated high spatial variability, with a prevalent deep chlorophyll (and phytoplankton biomass) maximum at ~80 m. Depth-integrated primary production within the study region ranged from 360 to 760 mg C m-2 d-1, which was on average 2.5 times higher than rates measured in continental shelf and off shorewaters north of the canyon.Aggregations of krill and other acoustic backscatter targets were concentrated near the head of the canyon at a range of depths, which may have been promoted by the circulation. The findings here are consistent with seasonal variations in wind and insolation, along with variations in the Leeuwin Current, influencing the seasonal changes and mesoscale features within the region, while the canyon promotes localised upwelling, and enhances both pelagic production and physical aggregation of plankton to attract the whales. Canyon processes must be combined with outside factors to allow upwelled nutrients to reach the photic zone. It is concluded that a combination of factors, rather than one factor alone, contributes favourably tothe appearance of feeding blue whales in the Perth Canyon during the summer.